Fundamental disagreement about monetary policy and the term structure of interest rates - Shuo Cao; Richard K. Crump; Stefano Eusepi; Emanuel Mönch (Federal Reserve Bank of New York, 2021)
Using a unique data set of individual professional forecasts, we document disagreement about the future path of monetary policy, particularly at longer horizons. The stark differences in short rate forecasts imply strong disagreement about the risk-return trade-off of longer-term bonds. Longer-horizon short rate disagreement co-moves with term premiums. We estimate an affine term structure model in which investors hold heterogeneous beliefs about the long-run level of rates. Our model fits U.S. Treasury yields and the short rate paths predicted by different groups of professional forecasters very well. About one-third of the variation in term premiums is driven by short rate disagreement.
Keywords: D83; D84; E43; G10; G12; 330; disagreement; heterogeneous beliefs; noisy information; speculation; survey forecasts; yield curve; term premium